A new species of Acanthostigma (Tubeufiaceae, Dothideomycetes) from the southern hemisphere - Sanchez, Romina Magali (2012)
A new species belonging to the bitunicate ascomycetes genus Acanthostigma is described from bark of two Nothofagus species from Argentina. Its identity as a new species is confirmed based on both morphology and molecular sequence data. Acanthostigma patagonica differs from other species in the genus by having larger ascomata and setae and wider ascospores that are asymmetrical. An amended key to Acanthostigma species is provided along with a discussion of other species previously described from South America.